Cerrahi girişim uygulanan hastalarda periferik venöz kateterizasyonda kullanılan teflon-vialon kataterlerin flebit ve enfeksiyon riski açısından karşılaştırılması - Coşkun, Hatice (My University, 2005)
Bu çalışma, cerrahi girişim uygulanan hastalarda, periferik venöz kateterizasyonda kullanılan Teflon-Vialon kateterlerin flebit ve enfeksiyon insidansının belirlenmesi amacıyla deneysel olarak yapılmıştır. Araştırma; İstanbul Kasımpaşa Deniz Hastanesi'nde 1 Eylül 2004 - 30 Mart 2005 tarihleri arasında, Genel Cerrahi ve Ortopedi servislerinde planlı cerrahi operasyon geçiren ve periferik venöz kateter takılan toplam 148 hasta ile yapıldı. Onayları alındıktan sonra hastalara preoperatif dönemde 18 ve 20 numaralı teflon ve vialon kateterler hemşireler tarafından dönüşümlü olarak takıldı. Kateter bölge gözlemi; araştırmacı tarafından her gün, İnfüzyon Hemşireler Birliği (INS) Flebit Skalasına göre (ağrı, kızarıklık, şişlik, sıcaklık, renk değişikliği, palpable venöz cord) yapıldı ve kateter çıkarıldıktan sonra 3 gün boyunca devam etti. Kateterler çıkarıldıktan sonra kültür alınarak mikrobiyoloji laboratuarına gönderildi. Araştırmanın verileri araştırmacı tarafından geliştirilen veri toplama formuna kayıt edilmiştir. Sonuç olarak; kateterlerin %21,6'sında flebit oluştu, flebitin ortalama 3,24±1,09 günde geliştiği belirlendi. Flebit gelişen kateterlerin %19.2'si vialon kateter, %24'ü teflon kateter grubundandı. Teflon kateterlerin %4'ünde mikroorganizma ürerken, vialon kateterlerde hiç üreme olmadı. Flebit ve enfeksiyon riski vialon kateterlerde daha düşük görülmesine karşın, gruplar arasındaki fark istatistiksel olarak anlamlı bulunmadı. Çalışmada, 40-49 yaş grubu hastalarda (%47.1), kadınlarda (%40.9), kubital bölgeye takılan kateterlerde (%64.3), kateterizasyon süresinin 73-96 saat olduğu durumlarda (%46.2), antibiyotik-antienflamatuar analjezik-anestezik grubu ilaçların kullanımında (%46.2), antibiyotiklerin ortalama 3.53±1.29 gün ve üzerinde kullanıldığı durumlarda, flebit riskinin önemli derecede arttığı saptanmıştır.

TEZ KONU BAŞLIĞI : A COMPARISON OF TEFLON AND VIALON CATHETERS REGARDING TO PHLEBITIS AND INFECTION RISK WHICH ARE USED IN PERIPHERAL VENOUS CATHETERIZATION OF PATIENTS WHO HAD A SURGICAL OPERATION SUMMARY This study has been performed experimentally to determine the phlebitis and infection incidance with the Teflon-Vialon catheters used in peripheral venous catheterization which were inserted to patients who had a surgical operation. The study was conducted on 148 patients who had an elective surgical operation and who were inserted peripheral venous catheters consequently in the surgical and orthopedic services between September 1st,2004 and March 30th,2005 in Kasimpasa Naval Hospital. Teflon and Vialon catheters which were 18 and 20 gauge were inserted to the patients alternately by the nurses in the post-operative period after their approval to be involved in the study was taken. The catheterization site was observed daily by the researcher according to the INS (Intravenous Nursing Society) Phlebitis Scale (pain, erythema,edema,streak formation,palpable venous cord ) and continued regularly in the following three days after removal. semi-quantitative culture was sent to the microbiology lab. The datas obtained from the research were recorded on the data forms which were developed by the researcher. According to the results of the study; it was determined that phlebitis developed in 21,6% of catheters, average phlebitis development period was determined as 3,24±1,09 days. Catheters in which phlebitis developed were 19,2% made of Vialon and 24% were made of Teflon material. While microorganisms isolated in 4% of Teflon catheters, no isolation occured in the Vialon catheters. Although the phlebitis and infection risks of the Vialon catheters were measured less in the study, there was no significant difference between the two groups statistically. The factors increasing the phlebitis risk were also evaluated in the study. It was determined that factors such as; 40-49 years of age (47,1%), female sex (40,9%), catheterization in the cubital site (64,3%), catheterization duration between 73-96 hours (46,2%), administration of antibiotic-antienflamatory analgesic-anastesic drugs and administration of antibiotics for 3.53±1.29 days or longer increase the phlebitis risk significantly.
Keywords: Cerrahi Hemşireliği; Flebit; Kateter; Teflon -Vialon